Impact of conflict on agriculture in Mali - Masset, Edoardo; Gelli, Aulo; Tranchant, Jean-Pierre; Diallo, Amadou Sekou (International Food Policy Research Institute, 2019)
Our paper aims to investigating the impact of conflict on population displacement, agricultural production and agricultural assets, and the mitigating effect of food aid. The paper is structured in the following way. In the next section we provide a description of the survey data used in the analysis. Section 3 describes the interplay of conflict and emergency aid in the area. Section 4 analyses the impact of conflict on agriculture, while section 5 investigates to what extent emergency aid mitigated the negative impact of conflict on agriculture. Section 6 discusses the limitations of the study and suggests some potential future lines of research.